PENGARUH PUPUK DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI JAHE ASAL KULTUR JARINGAN - HOBIR HOBIR; SITTI FATIMAH SYAHID; IKA MARISKA (Jurnal Penelitian Tanaman Industri, 1998)
An alternative to produce healthy planting materials of ginger is through tissue cultue. However, the information on productivity and cultural practices or such mateial is still limited. Among the cultural aspects, fertilizer application and plant spacing mostly afect plant growth and yield. The objective of this study, was o evaluate the effect of fertilizer application and plant spacing on the growth and yield of rhizome. Planting materials (tissue culture and conventionally derived rhizomes) wee espectively planted in two plant spacings (60 cm x 40 cm and 40 cm x 30 cm) and applied with two levels of ertilizers (with and without fertilizer). The fertilizers applied were 40 tons stable manure and urea, TSP, and KCI wee 400 kg/ha. The expeiment was conducted in the Sukamulya Expeimental Station (Sukabumi)) rom August 1994 to  December 1995 in a split-split plot design in four replicates. Die main plot was ertilizer application, the sub plot was plant spacing and the sub-sub plot was planting material. The parameters used for evaluating the response of the plants to the treatments wee growth components (plant height stem circumeence, number of tillers and leaf size), and yield components (weight and size of rhizome). Results revealed that plants rom tissue culture generally showed the lower growth performances with lower yield and size of rhizomes, except in the number of tillers. The application of urea, TSP, and KCI at a respective rate of 400 kg/ha significantly increased plant height (rom 49 o 60 cm), stem circumerence (rom 2.2 o 2.6 cm) and weight of rhizome/clump (rom 206 o 379 g). Plant spacing did not affect any parameter observed. Interaction efect was shown between the source of planting materials and fertilizer application on the number of tillers and the thickness of rhizomes. For the plants rom tissue cultue ertilizer application significantly increase the number of tillers (rom 18 o 30 tillers/clump) and for those rom conventional rhizome the treatment did not afect the parameter. On the other hand, for the plants rom conventional rhizome ertilizer application improved the thickness of rhizome (rom 2.51 o 3.17 cm) while for those rom tissue cultue the teatment did not give any efect on the parameter. The thickness of rhizome was also afected by the interaction between fertilizer application and plant spacing. For the plant spacing of 40 cm x 30 cm, ertilizer application inceased the thickness of rhizome (from 1.68 to 2.11), while those of 60 cm x 40 cm, the teatment did not afected the parameter.